Profile and perception of egg consumption by students of the Federal Institute of Education, Science and Technology of Maranhão Campus São Luís – Maracanã (Research, Society and Development, 2022)
There are several myths about hygienic nutritional aspects other than consumption and eggs. Interviews are a way to get to know your wants and needs. Thus, the objective is to study the profile and perception of egg consumption by students Federal Institute of Education, Science and Technology of Maranhão campus São Luís - Maracanã. After the project was approved by the Research Ethics Committee for human beings under number (registration number: 56255921.9.0000.5085). The research was carried out with 118 18-year-old students from IFMA's Higher Education and Technical Education modalities. One was released with 24 questions related to egg consumption habits. Among the results it can be observed that the consumer is aware of the dangers that can occur in the ingestion of poorly handled eggs (82.20%). They are more attentive to the identity of the eggs (57%). They know that eggs do not contain music (71.2%). They showed buying habits and higher consumption of 4 to 7 eggs per week. Appearance is the most important aspect when choosing eggs (42.40%). It was concluded that the egg is part of the students' basic diet, they are aware of the identity and characteristics of eggs and the importance of labels. The storage of eggs outside or on the refrigerator door is the aspect of greatest inadequacy related to egg conservation. Students understand myths about eggs and the use of hormones in egg production. On the other hand, most are unaware of enriched eggs.